Fracture characteristics of freestanding 8 wt% Y2O3-ZrO2 coatings by single edge notched beam and Vickers indentation tests - Wan, J.; Zhou, M.; Yang, X.; Dai, C.; Zhang, Y.; Mao, W.; Lu, Chunsheng (Elsevier S.A., 2013)
The freestanding 8 wt% Y2O3–ZrO2 (8YSZ) samples prepared by an air plasma sprayed technique were measured by single edge notched bending tests. The strain evolution and cracking near a pre-existed notch region were in-situ monitored by digital image correlation. With the help of digital image data, the critical bending loads of these notched freestanding 8YSZ samples can be accurately determined. The fracture toughness and micro-hardness of freestanding 8YSZ samples were tested by Vickers indentations. The normalized fracture toughness calculated according to the Weibull statistics is in agreement with the testing and available data. These results are instructive in predicting the lifetime and durability of thermal barrier coatings with irregular geometric structures.